Comparison of different rough surface models for computer simulation of light collection in a scintillator/light guide system - Kilimchuk, I.V.; Tarasov, V.A. (Functional Materials, 2007)
A model of the reflecting surface has been developed that takes into account the data of the microface slope distribution for glass surfaces treated by various abrasives. These distributions were used to simulate the light collection in the scintillators. The proposed model efficiency has been confirmed by the agreement between the calculated light scattering indicatrices for the surfaces with various roughness degree and the experimental results obtained before. The comparison between the calculated results of the light collection for different rough surface models and the experimental ones in a scintillator/conical light guide system with different types of lateral surfaces indicates that the best agreement is obtained when the developed model is used.